Amidas cinâmicas sintéticas e investigação da atividade antifúngica frente às cepas de Candida spp - Barboza, Joice Nascimento (2020)
In the last decades there has been an increase in the incidence of fungal diseases, showing itself as an important cause of morbidity and mortality in humans, affecting more than one billion individuals worldwide. Yeasts of the genus Candida spp. they are opportunistic pathogenic fungi, which stand out as the most isolated in clinical samples (prevalence of 40-70%). The development of fungal resistance associated with the high toxicity, cost and effectiveness of antifungals on the market, has been driving the search for new therapeutic alternatives. Cinnamic acids are a group of aromatic carboxylic acids widely found in vegetables, which have structural diversity, low toxicity and various biological activities described, with emphasis on anti-Candida activity. Thus, the present study aimed to prepare a collection of thirteen amides(1- 13), structurally related, and to evaluate the antifungal activity of these compounds against three species of Candida spp.: C. albicans, C. krusei and C. tropicalis, as well as to establish the structure-activity relationship of the evaluated substances. The amides were prepared using the acid chloride reaction methodology and the compounds were characterized by infrared and, 1H and 13C Nuclear Magnetic Resonance spectroscopic techniques and showed yields ranging from 36-85.6%. Among the thirteen substances obtained, two are unprecedented in the literature (4 and 13). In the antifungal test, the determination of the minimum inhibitory concentration (MIC), the determination of the minimum fungicidal concentration (CFM) and the test to determine the mechanism of action (sorbitol and ergosterol) were performed. Through the results of bioactivity, it can be observed that amides 1 and 4 demonstrated a fungicidal effect against strains of Candida spp. Compound 4 showed better antifungal activity with MIC values=CFM=0.67 mM, 0.33 mM, 1.34 mM against C. albicans, C. krusei and C. tropicalis, respectively. It was found through reason (CFM/CIM < 4), that the molecules had a fungicidal effect. The molecular docking study suggested that the possible mechanism of action of bioactive compounds occurs via multi-targets with the inhibition of HOS1 as the main biological target. Therefore, it can be concluded that it was possible to establish chemical characteristics that can serve as a reference for advancing development of new antifungal prototypes with better biological action against Candida species.